The influence of the quality of Tuberculosis services with adherence to taking Anti-tuberculosis drugs - Ridhona Fajar Sari; Martini Martini; Mursid Raharjo (Universitas Muhammadiyah Surabaya, 2023)
Indonesia was the second world's highest TB case in 2021. Tuberculosis therapy that takes a long time can cause patients to drop out of treatment. Hospitals conduct quality evaluations regularly and improve the quality of health service personnel to realize excellent health services. This literature review aims to determine the effect of the quality of tuberculosis services on patient compliance with anti-tuberculosis drugs. This literature review was written using a systematic approach. The databases used were Google Scholar, Science Direct, Proquest, and Scopus. The total number of articles obtained was 8 out of 64 based on inclusion criteria. The things that affect the regularity of taking medication based on the eight journal articles above are as follows: 1) the assurance dimension is 50%, 2) the dimensions of empathy and reliability amounted toÂ 37.5%, 3) the responsiveness dimension is 25%, 4) patient satisfaction, direct evidence and service quality amounted to 12.5%. Adherence to taking medication is influenced by: 1) the presence of supporters of taking medication, 2) difficulty taking the medication regularly, (3) perceived benefits of taking anti-tuberculosis drugs, and 4) self-perception related to healing. The dimensions of assurance, empathy, and reliability have the most influence on the regularity of taking anti-tuberculosis drugs.